Product Variety and Economic Growth Empirical Evidence for the Oecd Countries - Funke, Michael (International Monetary Fund, 2000)
This paper uses panel data for 19 OECD countries and finds support for the hypothesis that a greater degree of product variety relative to the United States helps to explain relative per capita GDP levels. The empirical work relies upon some direct measures of product variety calculated from 6-digit OECD export and import data. Although the issue is still far from being settled, the emerging conclusion is that the index of relative product variety across countries is significantly correlated with relative per capita income levels